(3GdbhGYO GdSfjI aj bQGAI MaU Yf YGUe ef WQjb GdTGWHjIs - (3EHQGgje Hf ESeGYjd GdYOhis; (3GdbGSe Hf ajQg Hf Nda Hf CMeO GdQYjfj, CHh eMeO GdTGWHj,J (B590 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CfRd GdbQBf GdYXje QMeI ddGeI hJjSjQkG hagekG WQb bQGAJg s
(3BNQgG (B:s
(3hGdeQLh eef hba Ydi gPg GdQSGdI Cf jPcQ LGeYgG HNjQ hEf cGf HgG Rdd CUdMg s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B180 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B110s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs